Electrospray ionisation-cleavable tandem nucleic acid mass tag-peptide nucleic acid conjugates: synthesis and applications to quantitative genomic analysis using electrospray ionisation-MS/MS. - Thompson, A; Prescott, M; Chelebi, N; Smith, J; Brown, T; Schmidt, G (2007)
The synthesis and characterization of isotopomer tandem nucleic acid mass tag-peptide nucleic acid (TNT-PNA) conjugates is described along with their use as electrospray ionisation-cleavable (ESI-Cleavable) hybridization probes for the detection and quantification of target DNA sequences by electrospray ionisation tandem mass spectrometry (ESI-MS/MS). ESI-cleavable peptide TNT isotopomers were introduced into PNA oligonucleotide sequences in a total synthesis approach. These conjugates were evaluated as hybridization probes for the detection and quantification of immobilized synthetic target DNAs using ESI-MS/MS. In these experiments, the PNA portion of the conjugate acts as a hybridization probe, whereas the peptide TNT is released in a collision-based process during the ionization of the probe conjugate in the electrospray ion source. The cleaved TNT acts as a uniquely resolvable marker to identify and quantify a unique target DNA sequence. The method should be applicable to a wide variety of assays requiring highly multiplexed, quantitative DNA/RNA analysis, including gene expression monitoring, genetic profiling and the detection of pathogens.